THE PLACE AND ROLE OF LABOR INTELLECTUALIZATION IN ENSURING WORLD INNOVATIVE DEVELOPMENT - A. Boiko (Вестник Северо-Кавказского федерального университета)
As a result of writing the article, theoretical and practical recommendations were developed for the study of the place and role of intellectualization of labor in ensuring global innovative development. It was found that the main source of innovative development is in the intellectual resources of society, and an increase in the intellectual level of the workforce at all levels (mega -, macro - and micro levels) will help meet demand in the world labor market. The block diagram ofthe employee's innovative development process is presented. A graphic interpretation of the dual interdependence between the creation of innovations and the use of the possibilities of intellectual resources in the modern international economy is proposed.